Analysis of the Effect of Service Quality, Product Availability, Location and Store Atmosphere in Increasing Customer Loyalty at the Labuhanbatu Distro Instore Store - Surya, Adi; Broto, Bayu Eko; Arjuna, Syukron (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of service quality, product availability, location, and store atmosphere in increasing customer loyalty at the Instore Distro Labuhanbatu Store. The background of this study is based on the increasingly fierce competition in the fashion retail business, so every business actor needs to pay attention to factors that can create a positive shopping experience and encourage the formation of customer loyalty. This study uses a quantitative method with a survey approach, involving customer respondents who have shopped at Instore Distro. Data were collected through questionnaires and analyzed using multiple regression techniques to determine the magnitude of the influence of each independent variable on customer loyalty. The results show that service quality, product availability, location, and store atmosphere have a positive and significant effect on customer loyalty. Friendly and professional service quality increases customer satisfaction, the availability of complete and appropriate products encourages repeat shopping interest, a strategic location facilitates accessibility, while a comfortable store atmosphere creates a pleasant shopping experience. Simultaneously, these four variables are proven to contribute to the formation of customer loyalty at the Instore Distro Labuhanbatu Store.